Research on Cavitation Performance of Bidirectional Integrated Pump Gate - Huahuang Lai; Haoshu Wang; Zhen Zhou; Rongsheng Zhu; Yun Long (Energies, 2023)
A pump gate is a device that controls the flow of water. It can stop the flood when it comes, drain the ponding gathered in the city, and improve the water circulation of the city. Traditional pumping stations require a large land area, and their pump houses and gates need to be designed separately. Furthermore, the construction period of traditional pumping stations is lengthy, and the maintenance costs are high. It can no longer meet the needs of modern cities for water environment management. Therefore, it is imperative to design a new type of pump gate. The integrated pump gate introduced in this paper is an integrated construction of gates and pumps to achieve automatic control and bidirectional operation. The research mainly consists of three parts: design of pumping station, theoretical analysis, and numerical calculation. By studying the unstable flow inside the integrated pump, the characteristics and the degree of cavitation occurrence are predicted. This can provide a reference basis for the optimal design and stability operation of the integrated pump gate. To investigate cavitation in an integrated pump gate, numerical simulations were performed for multiple operating conditions using the SST turbulence model. Constant numerical simulations of cavitation through numerical calculation, the characteristic curves of the integrated pump gate under forward and reverse operation at different flow points were obtained, and flow field analysis was performed for the model pump at 1.0 Q. The location and degree of cavitation occurrence were predicted. In this study, a preliminary analysis was conducted to investigate the influence of cavitation on the internal flow characteristics of integrated gate pumps. The research collected data related to cavitation characteristics, streamline patterns, and blade pressures. Additionally, the study explored the characteristics of cavitation phenomena, laying the foundation for the optimization of the design of bidirectional operation in integrated sluice gate pumps for future practical engineering applications.